Importance of diagnostics in epidemic and pandemic preparedness. (2nd February 2019) - Kelly-Cirino, Cassandra D; Nkengasong, John; Kettler, Hannah; Tongio, Isabelle; Gay-Andrieu, Françoise; Escadafal, Camille; Piot, Peter; Peeling, Rosanna W; Gadde, Renuka; Boehme, Catharina
Abstract : Diagnostics are fundamental for successful outbreak containment. In this supplement, 'Diagnostic preparedness for WHO Blueprint pathogens', we describe specific diagnostic challenges presented by selected priority pathogens most likely to cause future epidemics. Some challenges to diagnostic preparedness are common to all outbreak situations, as highlighted by recent outbreaks of Ebola, Zika and yellow fever. In this article, we review these overarching challenges and explore potential solutions. Challenges include fragmented and unreliable funding pathways, limited access to specimens and reagents, inadequate diagnostic testing capacity at both national and community levels of healthcare and lack of incentives for companies to develop and manufacture diagnostics for priority pathogens during non-outbreak periods. Addressing these challenges in an efficient and effective way will require multiple stakeholders—public and private—coordinated in implementing a holistic approach to diagnostics preparedness. All require strengthening of healthcare system diagnostic capacity (including surveillance and education of healthcare workers), establishment of sustainable financing and market strategies and integration of diagnostics with existing mechanisms. Identifying overlaps in diagnostic development needs across different priority pathogens would allow more timely and cost-effective use of resources than a pathogen by pathogen approach; target product profiles for diagnostics should be refined accordingly. We recommend the establishment of a global forum to bring together representatives from all key stakeholders required for the response to develop a coordinated implementation plan. In addition, we should explore if and how existing mechanisms to address challenges to the vaccines sector, such as Coalition for Epidemic Preparedness Innovations and Gavi, could be expanded to cover diagnostics.